Revitalisasi Kawasan Kumuh dengan Pendekatan Konsolidasi Tanah Vertikal di Kota Samarinda - Dzulfajrie Rahim; Juang Akbardin (Arsir: Jurnal Arsitektur, 2025)
Slum areas in major cities often reflect policy failures and a lack of political will. This study aims to examine the revitalization of the Karang Mumus area in Samarinda through a vertical land consolidation approach (KTV). The research employs a qualitative method, utilizing observations and literature studies from secondary data and field reviews. Findings indicate that the Karang Mumus area covers 8.72 hectares and has been prioritized for intervention through a collaborative funding scheme. Location scoring analysis, based on key and supporting factors, shows that the readiness of potential new locations ranges from 50% to 75%. The implications of these findings suggest that the implementation of KTV requires significant efforts and support from various stakeholders to improve slum settlements into more livable, clean, orderly, safe, and healthy environments. This study provides valuable insights for policymakers in planning and prioritizing slum revitalization in major cities.